2004
DOI: 10.1086/421910
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of HIV‐1 by Primary Human Uterine Epithelial Cells and Stromal Fibroblasts

Abstract: Women can become infected with human immunodeficiency virus type 1 (HIV-1) after the heterosexual transmission of virus from an infected male partner. To understand the events that result in transmission of HIV-1 across the female reproductive tract, we characterized the life-cycle events of HIV-1 in primary cultures of human uterine epithelial cells and stromal fibroblasts. Epithelial cells and stromal fibroblasts released virus particles after exposure to either X4-or R5-tropic strains of HIV-1. Virus releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…6). In contradiction with our data, Asin et al [2004] showed that uterine epithelial cells, infected by an X4 strain of HIV, were able to produce infectious particles and to transmit the infection to PBMCs. However, the level of HIV production reported in the latter study was relatively low and highly variable from one cell line to another, questioning the relevance of this observation with regards to a significant participation of these cells in the initial spread of X4 strains.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…6). In contradiction with our data, Asin et al [2004] showed that uterine epithelial cells, infected by an X4 strain of HIV, were able to produce infectious particles and to transmit the infection to PBMCs. However, the level of HIV production reported in the latter study was relatively low and highly variable from one cell line to another, questioning the relevance of this observation with regards to a significant participation of these cells in the initial spread of X4 strains.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding was not linked to exogenous genomic viral material since no proviral DNA was found in cells treated with AZT or rhSDF-1 and incubated with LAI. Accordingly, using primary human uterine cells, Asin et al [2004] demonstrated the specific integration of an X4 (and not R5) HIV isolate. Although our results evidenced a more efficient integration of HIV DNA inside HEC1A compared to CaSki, SiHa or normal human vaginal cells, the use of a sensitive alu-gag PCR technique allowed us to demonstrate a weak but significant X4 HIV integration inside the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first round of the HIV-1 integration PCR was performed by using the Alu sense primer (5Ј-GCCTCCCAAAGTGC TGGGATTA-3Ј) (IDT), which binds to short DNA sequences occurring in multiple locations throughout the human genome, and the HIV-1 Gag antisense primer (5Ј-CCTGCGTCGAGAGAGCTCCTCTGG-3Ј) (IDT) (3). Five microliters of first-round product was then used in nested PCR, with the LTR sense primer M667 (IDT) and the antisense primer AA55 (IDT) (3). Products from the second-round PCR were run on 1% agarose gels with ethidium bromide to detect an expected 140-bp fragment.…”
Section: Methodsmentioning
confidence: 99%
“…There are conflicting reports regarding the ability of ECs to be infected by HIV, but some studies have shown that ECs could be targets for productive infection [14,15]. Studies using primary ECs suggest that ECs are permissive to X4 HIV isolates but not R5 HIV and that captured R5 viruses are readily released [14].…”
Section: Interaction Between Hiv and Ecsmentioning
confidence: 99%